THE ORGANIC UNITY OF DIVINE AND METAPHORICAL LOVE IN THE NA’T CHAPTERS OF THE EPIC «LAYLI AND MAJNUN» - Gullola Olimova Shuhrat qizi (International Journal of Literature and Language Studies, 2026)
This thesis provides information about the na’t chapters within «Layli and Majnun,» the third epic of Navoi’s «Khamsa,» and analyzes their artistic features through poetic devices. It also demonstrates that the organic connection between the divine love expressed in the na’ts and the metaphorical love is reflected in the plot.